The remarks on criminal responsibility for breaking intellectual property - Jurewicz, Justyna (Acta Universitatis Lodziensis. Folia Iuridica, 2012)
The article contains the strict description of issues connected with Polish law of intellectual property in aspects of possible criminal responsibility for breaking this law. The text describes the elements of crimes against intellectual property, that are included in Polish Act of Copyright and Allied Rights in Sections 115–119, with indication of penalties which threaten for committing such crimes. The article is an attempt on performing of difficulties which can be met in combining the interpretation of public and private regulation existing in the same act – on example Act of Copyright and Allied Rights. One presents connections between general regulations that are typical for civil (private) law and detailed regulations of criminal law. There are following conclusions placed in the text: The Act of Copyright and Allied Rights contains a few types of crimes against intellectual property, which description leaves too much innuendos. It causes difficulties in giving interpretation compatible with the principle of nullum crimen sine lege stricta and certa. The most obvious instance is the crime provided in Sec. 115.3 of the Act of Copyright and Allied Rights; The regulations of criminal responsibility in the Act of Copyright and Allied Rights seem to be not consulted with persons working on criminal regulation both in theory and practice. They are different from traditional criminal regulations and that is why they cannot be easily used according to rules of interpretation customary functioned in practice of criminal procedure. Besides these regulations are written with using language that is not found it Polish Penal Code. It should be considered if there is a need to retain the criminal responsibility for breaking the regulation of the Act of Copyright and Allied Rights. It seems that the protection that is result of civil law is sufficient. There is difficult to precise the public interest that is threatened by the described crimes. It ought to be focused on the private interests of authors and other subject having proper rights attendant from the Act.